Accuracy of diagnosis of COPD and factors associated with misdiagnosis in primary care setting. E-DIAL (Early DIAgnosis of obstructive lung disease) study group - Nardini, Stefano; Annesi-Maesano, Isabella; Simoni, Marzia; Ponte, Adriana del; Sanguinetti, Claudio Maria; De Benedetto, Fernando (Respiratory medicine, 2018)
Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide and results in both substantial and increasing socioeconomic burden. Guidelines on COPD encourage primary care physicians to detect the disease at an early stage. Our main aim was to evaluate the accuracy of the diagnosis of COPD at the primary health care. 6466 patients were randomly selected in 22 Italian primary care practices (46% males, mean age 56 ± 16 years) and were asked about respiratory symptoms and risk for any chronic respiratory disease including COPD. After a prior evaluation, 701 patients (51% males, mean age 59 ± 15 years) were sent by General Practitioners (GPs) to Pulmonary Units (PU) for confirming the diagnosis. The agreement in diagnosing COPD between GPs and pulmonary diseases specialists was assessed by using Cohen's kappa (k) statistic. Lack of precision in COPD diagnosis resulted in 13% of over-diagnosis and 59% of under-diagnosis. GPs were quite good in correctly excluding the patients who did not have COPD (specificity = 87%), but less good in diagnosing the patients with COPD (sensitivity = 41%). The risk of under-diagnosis was higher in people with age >62 years and in current/ex-smokers, when compared to no COPD, whereas it was higher in subject <62 years old and in those with no previous spirometry when compared to correctly diagnosed COPD. Our results confirm that COPD misdiagnosis is common in primary care and that under-diagnosis is a major problem. It is necessary to enhance COPD diagnosis and to reduce misdiagnosis in primary care settings. •COPD is a silent killer that is often diagnosed too late and constitutes a major health concern nowadays.•Our results confirm that COPD misdiagnosis is common in primary care and in particular that under-diagnosis is a major problem. Lack of precision in COPD diagnosis resulted in 13% of over-diagnosis and 59% of under-diagnosis.•Having performed a previous spirometry and self-reported symptoms of chronic cough, phlegm and dyspnea were the only factors that significantly decreased the risk for undiagnosed COPD (by about 4 folds each).•Our findings have to be applied in clinical settings.